PENGARUH KUALITAS PRODUK, HARGA DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN KOPI KENANGAN MELALUI KERANJANG KUNING TIKTOK - Dewi, Adhita Maharani; Asmarawati, Sandragaluh (Politeknik Bisnis Indonesia, 2025)
The influence of price, quality, and promotion on the purchase of Sabdo Palon syrup proves that price is the strongest variable in influencing the purchase of herbal products[2]. In addition, price refers to the financial aspects required to achieve the stated goals. Coffee is one of Indonesia's export commodities. Kopi Kenangan is a coffee brand originating from Indonesia and is currently starting to enter the international market. With strong branding, Kopi Kenangan has succeeded in attracting consumers. The TikTok application is one of the social media used by Kopi Kenangan to reach consumers. On TikTok there is an affiliate program that is of interest to users, seeing this gap, Kopi Kenangan opened an offer as their affiliate by including a yellow basket on videos made by TikTok users. Based on this, the author examines the effect of product quality, price and promotion on the decision to purchase Kopi Kenangan through the Tiktok yellow basket. The results of this study state that the promotion and price variables are determining factors for the decision to purchase Kopi Kenangan